Effect of fertilization of Seaweed extracts and CuSO4 on some vegetative growth indicators of Citrus limon L. grafted seedlings on rootstock aurantifolia - Abrar Moneam Almoussawi; Ghalib BA Al-Abbasi (Kufa Journal for Agricultural Sciences)
Citrus aurantifolia rootstock seedlings were treated with Seaweed extracts and copper sulfate. Seaweed extracts were added as a ground feed during the growing season at four levels (0, 10, 20, and 30 ml. seedling-1) and copper sulfate sprayed at four concentrations (15,10,5, 0 ml. L-1) alone or in combination with the control (watering with water only) during the growing seasons 2020-2021. The results showed that the treatment of seedlings grafted on rootstock aurantifolia with Seaweed extracts and spraying with copper sulfate affected (height, stem diameter, area Leaf, root length, and chlorophyll content of leaves (the results also showed that the addition of Seaweed extracts at a concentration of 30 ml overlapping with copper sulfate spraying at a concentration of 15 ml. L-1 is recommended to improve the vegetative, root and nutritional growth of lemon citrus seedlings.